Chinese learners' perceptions towards teachers' language use in lexical explanations: A comparison between Chinese-only and English-only instructions. (December 2016) - Tian, Lili; Hennebry, Mairin
Abstract: This paper examines Chinese learners' contextualized perceptions of and preferences towards teachers' language use for explaining unknown lexical items, and compares the perceptions of 68 Chinese university students in the context of English-only versus Chinese-only lexical explanations. A questionnaire was administered to students to investigate their general language use preferences. 36 follow-up interviews were also conducted in order to examine students' perceptions in the context of more specific lexical explanations. While questionnaire responses suggested that a majority of students held positive attitude towards both types of explanations, interview data indicated more negative perceptions towards the lexical explanations they received. The perceived distinctions of learners towards the use of English and the use of Chinese as teachers' language choices for lexical explanations were uncovered with regard to the learning of lexis. The paper discusses the implications of the study for classroom practice specifically in the area of lexical explanations and situates the discussion in the broader context of the debate around L1 use in the L2 classroom.